Incorporating Representation-Based Instruction Into Mathematics Teaching - Ulusoy, Fadime; Incikabi, Lutfi (IGI Global, 2019)
Developing students' abilities in using and selecting appropriate representations and making transformations between representations is an important issue in mathematics education. Among the mathematical concepts, fractions have always reported as a challenging issue for students in the middle schools for a long time. In this sense, researchers have suggested the use of different representations in learning and teaching of fractions in order to enhance students' conceptual understandings of fractions. Based on this suggestion, we provide some activities for engaging middle school students with multiple representations of fractions by focusing on addition operation. These activities are focused on the need to identify appropriate instructional strategies to enhance students' communication and critical thinking, thus improving their academic performance in mathematics.
Keywords: 4. Education; 10. No inequality